Why Europe Waited for Five Centuries Before Acknowl-Edging the Wood Carvings of Black Africa as Works of Art (Journal of Science and Technology, 2016)
Although such an important person as Charles the Bold had by 1470, purchased some Black African wood carvings and though some of the sculptures were later displayed in some famous European museums and parlours, the continent waited till the beginning of the twentieth century before acknowledging the carvings as works of art. The reason for the five hundred years of delay include Europe’s condemnation of the carvings as barbarous fetishes devoid of aesthetic qualities, her conservative ethnocentric and complacent attitude, her ignorance of the carvings symbolic nature, her little or no predilection for exotic artifacts and her disrespect for Africans and their handiworks. Above all, Europe initially failed to acknowledge the carvings because they were socio-economically unimportant to her.